The Virtual Virtual Machine Project - Folliot, Bertil (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41200, 2000)
This paper presents the invited talk at the "Simposio Brasileiro de Arquitetura de Computadores e Processamento de Alto Desempenho (SBAC'2000)": the Virtual Virtual Machine approach for highly configurable operating systems. This is a joint work with action SOR – INRIA Rocquencourt. More information about the Virtual Virtual Machine project can be found at:  http://www-sor.inria.fr/projects/vvm